The Rhetoric of Meaning: Generative Anthropology and the Rhetorical Approach to Narratology - Ludwigs, Marina (Anthropoetics, 2020)
This paper compares rhetorical narratology to Generative Anthropology in order to point out important similarities between their underlying assumptions. It also shows how they can contribute to each other and together advance our understanding of narrative as a complex and heterogeneous genre of literature. The argument starts with situating the rhetorical approach to narrative theory in relation to other branches of narratology for the purpose of demonstrating its emphasis on the communicative character of narrative over its “content.” The communicative model of rhetorical narratology is similar in its underlying assumptions to the scene of representation in Generative Anthropology insofar as it presupposes a common cognitive environment or a shared ethical space. The paper further claims that although in practical terms, the method of reading employed by rhetorical narratologists does not need a minimal anthropological hypothesis to sharpen its interpretative focus, it would benefit from the intuitions of Generative Anthropology as an explanatory scaffolding to justify its praxis and theoretical observations. Thus Generative Anthropology’s originary hypothesis about the configuration of the scene can support two innovations by rhetorical theory: firstly, multiperspectivism engendered by narrative thinking, and, secondly, framing a rhetorical reading in terms of an oscillation between response and evaluation. In its turn, the rhetorical approach, which gives a great deal of attention to the dynamics of reader response, can prompt Generative Anthropology to contemplate whether or how individual paths to narrative closure affect meaning.